(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The given article regards a causes of professional burnout and analyzes some innovation methods of its prevention. The author regards the methodology of the Theatre of the Oppressed as a possible way of overcoming burnout symptoms of the volunteers. Volunteering is a popular phenomena all over the world. Each country with a civil society necessarily has a working volunteering institute. Currently, the volunteer institute is actively structuring and adjusting the relevant processes so that active people don’t hurt themselves and others due to lack of professionalism in our state. Over the past decades, theorists and practitioners have thoroughly studied the impact of professional stress on the health and identity of workers and volunteers of those professions which are in intensive communication and interaction with people. Volunteers, usually, work in non governmental organizations (NGOs), side by side with staff members. The negative phenomenon of today’s volunteering and the work of a non- governmental organization is the professional burnout, the prevention of which isn’t conducted. In such conditions, in a state of physical, emotional or motivational exhaustion, a volunteer or an employee of any NGO has a disruption of work productivity, fatigue, increased susceptibility to somatic diseases, and also consumes alcohol or other psychoactive substances. The author determines some modern methodology of psychological burnout prevention and presents the method of Boal’s Theater as the most efficient. He brings an example of burnout overcoming methods in the non governmental organizations.